Hemodynamic Response to Massive Bleeding in a Patient with Congenital Insensitivity to Pain with Anhidrosis - Yuki Sugiyama; Sayako Gotoh; Masatoshi Urasawa; Mikito Kawamata; Koichi Nakajima (Case Reports in Anesthesiology)
A patient with congenital insensitivity to pain with anhidrosis (CIPA) underwent revision of total hip arthroplasty under general anesthesia with only propofol. During surgery, neither elevation of stress hormones nor hemodynamic changes associated with pain occurred; however, when blood was rapidly lost, compensatory tachycardia was observed. Although patients with CIPA are complicated with autonomic disturbance due to dysfunction of postganglionic sympathetic fibers, this compensatory response indicated that the adrenal glands in patients with CIPA secrete catecholamine as part of a compensatory response during bleeding under general anesthesia.